2013
DOI: 10.4149/bll_2013_091
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of urothelial carcinoma

Abstract: From the archive of BB Biocyt company, 32 urinary bladder carcinomas (urothelium carcinomas, UC) and 7 cases of chronic cystitis were selected and examined in semiserial sections for the following antigens: 1) cell proliferation marker Ki-67 (expressed in the nuclei), 2) cell cycle regulator p16/INK4a polypeptide (expressed in the cytoplasm and nuclei), 3) urothelium marker p63 (expressed in the nuclei), 4) cytokeratin 7 (CK7). 5) cytokeratin 20 (CK20) and 6) high molecular weight cytokeratin (HMWCK). Invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(33 reference statements)
1
12
0
3
Order By: Relevance
“…Tissue microarray (TMA) of surgical specimens, and the expression of immunohistochemical tissue markers, may provide important clues to better understand the pathogenetic characteristics of UTUC and identify universal prognostic markers, which will aid in estimating more precise prognoses of UTUC after surgery. Therefore, in this study, 27 potential urothelial carcinoma-related tissue markers from previous urothelial carcinoma-related tissue studies and National Cancer Center bladder cancer panel [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were applied immunohistochemically (IHC) to the TMA of specimens from patients with UTUC who underwent RNU, in order to identify any significant prognostic tissue markers of survival, including intravesical recurrence-free survival (IVRFS), disease-free survival (DFS), and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue microarray (TMA) of surgical specimens, and the expression of immunohistochemical tissue markers, may provide important clues to better understand the pathogenetic characteristics of UTUC and identify universal prognostic markers, which will aid in estimating more precise prognoses of UTUC after surgery. Therefore, in this study, 27 potential urothelial carcinoma-related tissue markers from previous urothelial carcinoma-related tissue studies and National Cancer Center bladder cancer panel [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were applied immunohistochemically (IHC) to the TMA of specimens from patients with UTUC who underwent RNU, in order to identify any significant prognostic tissue markers of survival, including intravesical recurrence-free survival (IVRFS), disease-free survival (DFS), and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Alsheikh et al (2001), Pu et al (2008) and van Oers et al (2007) confirmed the association of CK20 with advanced stage and grade. Rajcani et al, (2013) found that CK20 was present in all invasive tumors. Ye et al, (2010) demonstrated that the intensity of CK20 and Ki-67 staining in cancerous tissues was significantly associated with tumor grades and distant metastasis of cancer bladder.…”
Section: Discussionmentioning
confidence: 96%
“…The expression pattern is altered only in malignant urothelium (Alsheikh et al, 2001;Southgate et al, 1999). Previous studies indicated that CK20 may be a specific biomarker for detecting bladder cancer (Rajcani et al, 2013;Eissa and Matboli, 2013;Schmidt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, p16 was evaluated using a score of 0 to 3 (no staining: score 0, staining between 0 and 10%: score 1, staining between 10 and 49%: score 2, strong staining: score 3) [8,17]. In other studies, expression below 10% was regarded as abnormal, while that above 10% was considered normal [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…P16a: p16 nuclear staining percentage was scored between 0 and 3 as follows: no expression: score 0, expression between 0 and 10%: score 1, expression between 10% and 49%: score 2, and strong expression, over 50%: score 3 [8,17].…”
Section: Immunohistochemical Scoring Systemmentioning
confidence: 99%